Implementação do protocolo de acolhimento com classificação de risco em uma emergência obstétrica - Amanda de Freitas Brilhante; Camila Teixeira Moreira Vasconcelos; Raylla Araújo Bezerra; Sâmua Kelen Mendes de Lima; Régia Christina Moura Barbosa Castro; Ana Fátima Carvalho Fernandes (Universidade Federal do Ceará, 2016)
Objective: to evaluate the implementation of reception with risk classification. Methods: evaluative study with a sample of 736 instruments for risk classification in a reference service. Results: authors identified greater search for care by pregnant women in the third trimester of pregnancy, being the pain and vaginal bleeding the main complaints. There was also a significant number of patients seeking care out of the period of pregnancy and childbirth. As risk classification, there was prevalence of the green color and the waiting time of 51 minutes. Conclusion: the clientele seeking gynecological and obstetric care in primary care needs further information about the signs and symptoms that characterize emergency care, because there has been great unnecessary demand for the service and the lack of training of professionals from the obstetric emergency unit led to waiting time above the recommended by the Brazilian Ministry of Health.